Inorganic Ions in Glasses and Polycrystalline Pellets as Fluorescence Standard Reference Materials - Reisfeld, R. (J Res Natl Bur Stand A Phys Chem, 1972)
The absorption and fluorescence of inorganic glasses and polycrystalline disks doped by heavy metal ions is discussed, and their use as fluorescence standards is evaluated. The advantages of the glass standards over other media is summarized. The glass standards are divided into two groups (1) glasses doped by trivalent rare earths such as Gd(3+), Tb(3+), Eu(3+), Sm(3+), and Tm(3+) which have narrow band optical spectra as a result of intraconfigurational transitions, and (2) glasses and polycrystalline disks doped by ions such as Tl(+), Pb(2+), Ce(3+), and Cu(+) which have broad spectral bands since the optical spectra originate from interconfigurationally allowed transitions. Optical and physical parameters, including matrix effects, quantum efficiencies, decay characteristics, Stokes’ shifts and spin-orbit versus orbit-lattice interactions due to the different transitions will be discussed. Group (1) glasses are suitable for use as standards where a narrow well-defined fluorescence range is required, and group (2) glasses are suitable for use as standards whenever a substance with a wide range of fluorescence is measured. Special emphasis will be placed on energy transfer between donor and acceptor ions.